Project Based Learning for Developing Learner Autonomy: University Level English Language Courses - Mahmud , Syeda Shabnam; Islam, Naushin Nazifa (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2022)
Along with the unprecedented advancements made in the sphere of English Language Teaching (henceforth ELT), the practitioners and educators have felt an undeniable demand of redesigning the teaching, learning, and evaluation strategies which have been dominating the teaching and learning process of EFL/ESL classes for the time unknown. Therefore, this field of education now puts its emphasis on enhancing learners' capacity of taking responsibilities of their own learning, which in turn promotes learner autonomy. All these changes contribute, to a large extent, to the promotion of pragmatic knowledge based learning to bring both the teacher and learners out from the erudite stereotypical practice of traditional assessments in the form of tests and examinations; hence, they are now in favor of alternative assessment that supports the notion of formative assessment. One of the most recognized tools of such assessment is Project Based Learning (PBL for now onwards), and it is not only a reflective praxis of alternative assessment but also is considered as a major learning tool for practical knowledge. It creates a scope for learners to learn from their peripheral surroundings by which they get influenced by in their everyday life, such as their social, political, communal, and familial settings. Therefore, this paper explores the possibilities as well as challenges of implementing PBL as a learning and an assessment instrument in English language classrooms at the tertiary level education in Bangladesh.